Issue Information. Issue 6 (28th June 2022) - Unknown
Abstract : Cover : Recent advances in proteomics allow the measurement of the abundance of thousands of proteins and phosphoproteins from multiple samples. Such analyses allow the study of the mechanisms underlying diverse signaling pathways during plant growth and development. In this issue, He et al . describe an experimental workflow for proteome and phosphoproteome studies, tailored to cereal crop tissues. The cover image illustrates this workflow, which starts with a maize leaf, from which proteins are extracted and digested, and phosphorylated peptides are then enriched over Titanium dioxide. These peptides are then detected by mass spectrometry, allowing the identification and quantitation of (phosho)peptides in proteome profiling experiments.